5, 5-Difluoro- and 5-Fluoro-5-methyl-hexose-based C-Glucosides as potent and orally bioavailable SGLT1 and SGLT2 dual inhibitors. Issue 17 (1st September 2020) - Xu, Guozhang; Du, Fuyong; Kuo, Gee-Hong; Xu, June Zhi; Liang, Yin; Demarest, Keith; Gaul, Michael D.
Graphical abstract: Abstract: (2S, 3R, 4R, 5S, 6R)-2-Aryl-5, 5-difluoro-6-(hydroxymethyl)tetrahydro-2H-pyran-3, 4-diols and (2S, 3R, 4R, 5S, 6R)-2-aryl-5-fluoro-5-methyl-6-(hydroxymethyl)tetrahydro-2H-pyran-3, 4-diols were discovered as dual inhibitors of sodium glucose co-transporter proteins (e.g. SGLT1 and SGLT2) through rational drug design, efficient synthesis, and in vitro and in vivo evaluation. Compound 6g demonstrated potent dual inhibitory activities (IC50 = 96 nM for SGLT1 and IC50 = 1.3 nM for SGLT2). It showed robust inhibition of blood glucose excursion in an oral glucose tolerance test (OGTT) in Sprague Dawley (SD) rats when dosed at both 1 mg/kg and 10 mg/kg orally. It also demonstrated postprandial glucose control in db/db mice when dosed orally at 10 mg/kg.